2021
DOI: 10.3390/e23121647
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Analysis of Protein Sequences Reveals a Hierarchical Organization

Abstract: Background: Analyzing the local sequence content in proteins, earlier we found that amino acid residue frequencies differ on various distances between amino acid positions in the sequence, assuming the existence of structural units. Methods: We used informational entropy of protein sequences to find that the structural unit of proteins is a block of adjacent amino acid residues—“information unit”. The ANIS (ANalysis of Informational Structure) method uses these information units for revealing hierarchically or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The positions of aligned sequences in the entropy plot can correlate with the structural and chemical characteristics of certain amino acids and their influence on the function of avUCP s. Therefore, regions that contain residue positions with low entropy are more likely to be involved in the functional sites of avUCP ( 83 , 84 ). Moreover, the absence of any region with more than 10 consecutive amino acids with an average entropy of >1 can be concluded as evidence of conservation in avUCPs .…”
Section: Discussionmentioning
confidence: 99%
“…The positions of aligned sequences in the entropy plot can correlate with the structural and chemical characteristics of certain amino acids and their influence on the function of avUCP s. Therefore, regions that contain residue positions with low entropy are more likely to be involved in the functional sites of avUCP ( 83 , 84 ). Moreover, the absence of any region with more than 10 consecutive amino acids with an average entropy of >1 can be concluded as evidence of conservation in avUCPs .…”
Section: Discussionmentioning
confidence: 99%
“…We assumed that the revealed hierarchical structures are associated both with the molecular evolution of NPCs and their functional activity. Results: Further studies showed that the use of the ANIS method made it possible to solve a number of important practical problems in various fields [2] -the design of protein molecules, studies of intermolecular interactions, and the study of the mechanisms of protein functioning. In addition, it was shown on model structural blocks that, with certain combinations of amino acid residues, they can only be located in the predominant conformational given topology [9].…”
mentioning
confidence: 99%